MOTIVASI DAPAT MEMEDIASI KOMPENSASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN (STUDI PADA PT. PACIFIK MEDAN INDUSTRI) - Widjaja, Dennis; Anton, Anton; Rezeki, Rezeki; Tjendana, Martinus; Sunijati, Elisha (Jurnal Manajemen dan Bisnis, 2024)
The purpose of this research was to determine the effect of compensation and training on performance with motivation as an intervening variable at PT Pacifik Medan Industri. The method used in this research is a quantitative descriptive method which is carried out through data collection using questionnaires and statistical testing data analysis. The population taken in this research were all 143 employees of PT Pacifik Industri Medan. With random sampling technique. The sampling method uses the Slovin formula with an error rate of 5%, so the sample is 105 people. The data analysis used is path analysis using the Sem application via Smart PLS 26. The results show that there is an influence between Compensation on Motivation, and Training has an influence on Motivation. Motivation can mediate compensation and training on employee performance, and there is an influence of motivation on performance, and there is a simultaneous relationship between compensation and training on employee performance.